2017
DOI: 10.1177/0030222817704336
|View full text |Cite
|
Sign up to set email alerts
|

A Determination of Hopelessness and the Perception of Illness in Cancer

Abstract: This study was performed with the objective of determining hopelessness and perception of illness in cancer patients. This was a descriptive and regressional study. The study was performed between January and June 2014 on 105 outpatients at the oncology clinic of Manisa Government Hospital in Turkey's western. A patient information form, the Beck Hopelessness Scale, and the illness perception questionnaire were used to collect data, and data analysis was performed using the program Statistical Package for Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
7
0
3
Order By: Relevance
“…Cancer stage may also contribute to differences in the prevalence of PTG and BF. The lower chance of cancer-free survival associated with more advanced cancer stage could increase the sense of hopelessness and perception of illness in a negative way [37]. As a result, cancer survivors with more advanced cancer stage might have reported lower BF and PTG.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stage may also contribute to differences in the prevalence of PTG and BF. The lower chance of cancer-free survival associated with more advanced cancer stage could increase the sense of hopelessness and perception of illness in a negative way [37]. As a result, cancer survivors with more advanced cancer stage might have reported lower BF and PTG.…”
Section: Discussionmentioning
confidence: 99%
“…Illness perceptions are personal and perhaps unique experiences derived from both concrete perceptual experiences of illness (e g, the experience of symptoms) and abstract sources of knowledge (e g, information from health care professionals such as predialysis education before the start of dialysis, or in the media) (29). Several studies demonstrated that illness perceptions had an effective compliance with treatments and was correlated with the results of various treatments (30). The results of the current study demonstrated that resilience was significantly and positively related to social support and illness perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Bizim çalışmamızın aksine Nehir ve ark. [33] (2019) kanser hastalarıyla yaptıkları çalışmada gelecekle ilgili duyguların 1,80±1,99, motivasyon kaybının 3,04±2,83 ve gelecekle ilgili beklentiler puan ortalamasının 2,67±1,77 olduğu saptanmıştır. Bu sonuçlara bakıldığında bu çalışmadaki hastaların daha umutsuz olduğu görülmektedir.…”
Section: Discussionunclassified
“…Yapılan çalışmalarda sosyal desteğin kanser tanısı alan bireylerin umudu üzerinde önemli bir faktör olduğu ve sosyal destek ile umut arasında pozitif bir ilişki olduğu görülmüştür. [33,42,43] Ancak bu çalışmada sosyal desteği olanların olmayanlara göre daha fazla umutsuzluk içinde olduğu saptandı. Literatürün aksine bu çalışmada elde edilen bulgulara göre, sosyal desteklerinin yeterli düzeyde olmadığını göstermektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation